2022
DOI: 10.1039/d1sm01523k
|View full text |Cite
|
Sign up to set email alerts
|

Hard superellipse phases: particle shape anisotropy & curvature

Abstract: We report computer simulations of two-dimensional convex hard superellipse particle phases vs. particle shape parameters including aspect ratio, corner curvature, and sidewall curvature. Shapes investigated include disks, ellipses, squares, rectangles,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…We have solved a subset of Eqns. (20), together with the pressure equality, p (c) = p (s) , between cloud and shadow phases, to find the set of moments {m (k,α) i } in both coexisting phases and at the parent number density ρ 0 . As will be shown in Sec.…”
Section: A Coexistence Calculationsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have solved a subset of Eqns. (20), together with the pressure equality, p (c) = p (s) , between cloud and shadow phases, to find the set of moments {m (k,α) i } in both coexisting phases and at the parent number density ρ 0 . As will be shown in Sec.…”
Section: A Coexistence Calculationsmentioning
confidence: 99%
“…As will be shown in Sec. A, we need to solve a total number of equations less than that in (20), which is a direct consequence of the peculiar form of the spt-area (3).…”
Section: A Coexistence Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter, in the case of HR of κ = 2, also exhibits 4-atic ordering with square dimers at perpendicular orientations, tesseling the whole area at close packing. Recent simulations showed that the 4-atic phase is stable up to κ ∼ 5 [40], while experiments on monolayers of granular cylinders of aspect ratios as large as 7 showed the existence of stationary states exhibiting 4-atic textures [22,26].…”
Section: A One-component Fluidsmentioning
confidence: 99%